The Dynamic Relations of the Northern European Countries and China Within Arctic Corridor Project in Regional Security Complex Perspective - Sakinah, Adzkia Rahma; Nugrahani, Henny Saptatia Drajati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The phenomenon of global warming has an impact on many things, including melting in the Arctic region which opens up opportunities for the opening of the Northern Sea Route in Arctic waters. China's presence in the Arctic region is increasingly massive in line with efforts to connect the Silk Road Belt Road Initiative in Europe with the Arctic region differently by Northern European countries. This study specifically discusses the dynamics of relations between Northern European countries—specifically referring to Nordic countries such as Denmark, Sweden, Norway, Finland, and Iceland—and China, especially regarding the Arctic Corridor project and geopolitics in the Arctic region. This study aims to characterize the presence or absence of securitization practices by Northern European countries against China related to the Arctic Corridor project. This will be discussed through the reactions, attitudes and policies shown by Northern European countries towards China in the framework related to the Arctic Corridor. The method used in this study is qualitative using a securitization approach, specifically the Regional Security Complex theory by Barry Buzan and Ole Waever to examine the problems discussed. Referring to this, the author asks the question, are there any securitization practices that occur in the dynamics related to the Arctic Corridor project between Northern European countries and China? Another question that is in line with this is how does the theory of securitization review the relationship between Northern European countries and China in the project? The hypothesis that emerges from the research question is that Northern European countries tend to have different attitudes in responding to China in the Arctic, specifically in the Arctic Corridor project. In this case Finland and Norway, which are the initiators of the project, tend to show their support for your presence in the Arctic, namely as financial supporters of the mega project. Meanwhile, Denmark, Sweden and Finland are just the opposite, which in this case considers China a threat in the context of regional security in both Northern Europe and the Arctic.